Eating in the Side Room : Food, Archaeology, and African American Identity - Warner, Mark S. (Book collections on Project MUSE., 2015)
Warner uses the archaeological data on food remains recovered from excavations in Annapolis, Maryland, as the point of departure for a broader look at the centrality of material culture in the construction of African identity in America.